Combined effects of obstacle position and equivalence ratio on overpressure of premixed hydrogen–air explosion. (19th October 2016) - Lv, Xianshu; Zheng, Ligang; Zhang, Yugui; Yu, Minggao; Su, Yang
Abstract: To investigate the combined effects of obstacle position and equivalence ratio on overpressure of premixed hydrogen–air explosion, an experimental study was performed in a 5 L duct with premixed hydrogen–air mixtures over a wide range of equivalence ratios, and along with the variation of a single obstacle position. In this paper, the equivalence ratios of the hydrogen–air mixtures were varied from 0.6 to 1.4, the obstacle was centrally located and was respectively 100, 200, 300 mm from the bottom end of the duct, the experiment without an obstacle was designed as a control experiment. For brevity, four configurations were defined according to the variation of the single obstacle position. The results indicated that the overpressure of premixed hydrogen–air explosion was closely related to the flame structure. The rise of dp / dt for hydrogen–air mixtures occurred when the flame started to feel the presence of the obstacle. The maximum overpressure could be observed at the moment that the two flames, generated from the gap between the obstacle and the inwall of the duct, just started to merge in the downstream region of the obstacle. It was also found that the venting overpressure might be barely observed under the combined effects of obstacle position and equivalence ratio. The rise time of dp / dt in a given configuration was gradually shortened with increasing equivalence ratio. Additionally, it was not simply a synergistic effect of obstacle position and equivalence ratio on peak overpressure. The peak overpressure increased with increasing obstacle position for lean hydrogen–air mixtures, and the maximum peak overpressure occurred in the downstream region of the farthest obstacle position. Interestingly, for the stoichiometric and rich mixtures, the peak overpressure reached the maximal when the obstacle was at the middle position. The occurrence of the maximum peak overpressure mainly depended on the maximum flame surface area within the duct. Highlights: Conjoint analysis was carried out on hydrogen–air flame structure and overpressure. Combined effects of obstacle position and equivalence ratio on overpressure were presented. A nonsynergistic effect of obstacle position and equivalence ratio on peak overpressure was found.